Odontogenic cysts, tumors and fibro-osseous lesions in children: a radiological pictorial case report - Abd. Aziz, Azian; Jesu, Vincent C.; S, Yogeswari (Springer, 2009)
We present pictorial illustrations of pediatric patients with odontogenic cysts, tumors and fibroosseous lesions presented in our institution. These include dentigerous cyst, odontogenic keratocysts,calcifying odontogenic cyst, ameloblastoma, adenomatoid odontogenenic tumor and ossifying fibroma. All the cases were confirmed on histology. Modalities for diagnosing these lesions include dental intraoral x-rays, orthopantomography (OPG) and computed tomography (CT) scans. CT scanning is helpful for very large lesions and to determine if bone is eroded by lesion. In our cases, some of these lesions were depicted on dental intraoral radiographs and orthopanthomography while CT was performed on some cases. Several studies were done previously to characterize and differentiate various cystic lesions and tumors in dental and maxillomandibular region based on the radiological features. However no conclusive information has been made to allow accurate diagnosis based only on radiological features. The aim of these pictorial illustrations is to highlight various radiological appearances of such lesions as in some centers the radiographs are usually seen only by the oral surgeons.